Estimation of population structure in emmer wheat germplasm conserved in the National Genebank of India - Jatin Tanwar; Sandhya Tyagi; Shivani Sharma; Preeti Jakhar; Gaurav Kumar; Sherry R. Jacob; Amit Kumar Singh; Shailendra K. Jha; Jyoti Kumari (Academia Biology)
Emmer wheat germplasm has received little attention with regard to exploring its genetic diversity toward enhancing utilization. Agro-morphological characterization was performed on 192 emmer wheat accessions during the winter season of 2019–2020, and subsequently 96 accessions were selected for morphological and molecular diversity analysis during the winter season of 2020–2021. Genetic diversity and population structure of 96 diverse Triticum dicoccum genotypes conserved in the National Genebank of India were estimated using 56 microsatellite (simple sequence repeat) markers. The number of alleles per locus ranged from one to six, with an average of 1.68 alleles. A total of 93 alleles were detected, with the highest polymorphic information content value (0.9912) observed for the Xcfd20 marker. Based on ‘STRUCTURE’ analysis, 96 dicoccum accessions were divided into two subpopulations. The analysis of molecular variance revealed that genetic differentiation among subpopulations was low and within subpopulations was high. A cluster analysis based on Jaccard’s dissimilarity index identified two clusters which were in congruence with the population structure. Indigenous and exotic collections were categorized into distinct subclusters within the same cluster with some overlapping suggesting limited genomic differentiation between these collections. Based on the present study, it is evident that cultivated emmer wheat showed low genetic diversity and a narrow genetic base. This might be due to limited cultivation in small pockets and emphasizes a need to broaden the genetic base of emmer wheat genetic resources for enhanced utilization.